Public Knowledge about Hepatitis B-Related Issues in Korea - C Chrusch; GY Minuk (Canadian Journal of Infectious Diseases)
Hepatitis B infection is endemic in many parts of the world, including Korea. Basic knowledge of the hepatitis B virus by the public is a prerequisite for the development of a successful vaccination program. A survey was conducted in rural Korea to examine public knowledge of hepatitis B etiology, symptoms, transmission, risk factors and prevention. It was found that knowledge independently correlated with education and female sex, but that overall knowledge of hepatitis B was poor. The preferred information sources in order of preference were physicians, television and public health nurses. This information may be useful in designing public health education and vaccination programs in developing populations.